Knowledge identification in medium-sized enterprises under the context of quality improvement – an exploration in manufacturing companies in China. Issue 5 (4th April 2021) - Wang, Chengbo; Mao, Zhaofang; Su, Hong; Tian, Ying
Abstract: As a fundamental element of knowledge management (KM), knowledge identification is a crucial issue in contemporary business organisations. Evidenced by research, medium sized enterprises (MEs) contribute constructively and significantly to economic development, society stabilisation and employment increase. Their healthy survival and growth are of critical importance to a nation. Among the approaches ensuring the successful development of MEs, quality improvement (QI) is a crucial one. However, what is and how to identify the knowledge most relevant to the MEs' QI, the drives and sources for identifying the QI knowledge (QIK) as well as the underpinning rationales, are currently lacking of sufficient study. The exploratory research reported by this paper has obtained and prioritised the up-to-date answers to these questions, leading to the enrichment of the theoretical understanding of KM approaches and practical guidance of their implementation in operations, under the context of QI in MEs.